Comparing fly-in fly-out and telehealth models for delivering advanced-practice physiotherapy services in regional Queensland: An audit of outcomes and costs. (January 2021) - Cottrell, Michelle; Judd, Perry; Comans, Tracy; Easton, Paula; Chang, Angela T
Introduction: Recruitment of advanced-practice physiotherapists to regional and rural healthcare facilities in Queensland, Australia remains a challenge. To overcome this barrier, two different service delivery models (Fly-In, Fly-Out (FIFO), Telehealth) were trialled by one regional facility. This study aims to describe the economic- and service-related outcomes of these two methods of service delivery. Methods: A retrospective audit was conducted where two nine-week time periods were selected for each service delivery model. Outcomes of interests include patient demographics and case-mix, service utilisation, clinical actions, adverse events and costs. Net financial position for both models was calculated based upon costs incurred and revenue generated by service activity. Results: A total of 33 appointment slots were recorded for each service delivery model. Patient case-mix was variable, where the Telehealth model predominately involved patients with musculoskeletal spinal conditions managed from a neurosurgical waiting list. Appointment slot utilisation and pattern of referral for further investigations were similar between models. No safety incidents occurred in either service delivery model. An estimated cost-savings of 13% for the Telehealth model could be achieved when compared to the FIFO model. Discussion: Telehealth is a safe, efficient and viable option when compared to a traditional in-person outreach service, while providing cost-savings. Telehealth should be seen as a service delivery medium in which sustainable recruitment of advanced-practice physiotherapists to regional and rural healthcare facilities can be achieved.